Improving the flexibility of graphene nanosheets films by using aramid nanofiber framework. (March 2021) - Xie, Kang; Liu, Yuhang; Tian, Yuxin; Wu, Xunen; Wu, Lingyu; Mo, Yanling; Sui, Guopeng; Du, Rongni; Fu, Qiang; Chen, Feng
Abstract: Graphene nanosheet (GNS) films exhibit good thermal and electric conductivities due to low oxygen content and defect density. However, the weak interlayer interaction forces have resulted in poor mechanical properties and flexibility for GNS films. In order to meet this challenge, aramid nanofiber (ANF) is introduced into the GNS films by solution mixing, then a small amount of water is added to adjust the aramid nanofiber framework (ANFF) in the solution. The results indicate that adding a small amount of water into the aramid nanofiber/dimethyl sulphoxide (ANF/DMSO) suspension can recover the hydrogen bonds between ANF, promoting the ANF to form a stable framework. This design strategy leads to a delectate balance between flexibility and electric, thermal conductivities. With the improvement of water or ANFF content, the mechanical properties of GNS/ANFF composite films are gradually increased. And the electric and thermal conductivities are not influenced by the water content but decrease with the increasement of ANFF content. Most importantly, the flexibility of GNS films is greatly improved with little sacrifice of electric and thermal conductivities by adding only 2 wt% ANFF (GNS-2). The tensile toughness of GNS-2 composite films is dramatically improved from 30.8 to 108.7 kJ m −3, while the electric and thermal conductivities of GNS films are slightly dropped from 827 to 569 S cm −1 and from 140 to 131 W m −1 K −1, respectively. Moreover, the excellent flexibility of the composite films can be maintained even after 1000 times of direct bending. The good over-all properties together with its easy preparation process endows GNS/ANFF composite films with potential applications in next-generation flexible electric devices.